The Fourth International Neonatal and Maternal Immunization Symposium (INMIS 2017): Toward Integrating Maternal and Infant Immunization Programs - Flor M. Munoz (American Society for Microbiology, 2018)
ABSTRACT Prevention of serious infections in pregnant mothers, newborns, and young infants through immunization during pregnancy and in early life has the potential to further reduce maternal and neonatal morbidity and mortality worldwide. In the past decade, research in this field has advanced substantially, from the understanding of the biology and immunology of pregnancy and early life, to the active development of several candidate vaccines, for which challenges and opportunities for global implementation are under consideration. Experts from academia, industry, regulatory and funding agencies, public health, and international organizations met in Brussels (Belgium) from 10 to 12 September 2017, at the 4th International Neonatal and Maternal Immunization Symposium (INMIS), to review the most relevant advances in maternal and neonatal immunization. The overarching focus of the conference was to identify the path forward to achieve integration of maternal and early life immunization strategies for the successful implementation of vaccines in antenatal care and pediatric programs for reduction of maternal and infant mortality worldwide. IMPORTANCE This report provides an overview of the proceedings of the 4th International Maternal and Neonatal Immunization Symposium, where presentations focused on the state-of-the-art research on the development and implementation of vaccines given during pregnancy for the protection of mothers and infants.